2017
DOI: 10.1210/en.2017-00773
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cells Show Increased Expression of Aromatase and Estrogen Receptor α in Prostate Epithelial Lesions of Male Aging Rats

Abstract: Besides androgens, estrogen signaling plays a key role in normal development and pathologies of the prostate. Irreversible synthesis of estrogens from androgens is catalyzed by aromatase. Interestingly, animals lacking aromatase do not develop cancer or prostatitis, whereas those with overexpression of aromatase and, consequently, high estrogen levels develop prostatitis and squamous metaplasia via estrogen receptor 1 (ERα). Even with this evidence, the aromatase expression in the prostate is controversial. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…However, animals aged 12 months and older showed a discrete but significant increase in the nuclear staining intensity of Recently, we showed that aging Wistar rats naturally develop epithelial prostatic lesions similar to many of those found in human prostate such as hyperplasia, intraepithelial proliferation, metaplasia, and atrophies. 27,35 Therefore, we also evaluated VDR expression in the prostate epithelium with histopathological alterations related to aging.…”
Section: Aging Affects the Expression Pattern Of Vdr In Rat Prostatmentioning
confidence: 99%
“…However, animals aged 12 months and older showed a discrete but significant increase in the nuclear staining intensity of Recently, we showed that aging Wistar rats naturally develop epithelial prostatic lesions similar to many of those found in human prostate such as hyperplasia, intraepithelial proliferation, metaplasia, and atrophies. 27,35 Therefore, we also evaluated VDR expression in the prostate epithelium with histopathological alterations related to aging.…”
Section: Aging Affects the Expression Pattern Of Vdr In Rat Prostatmentioning
confidence: 99%
“…Chrysin has been described as inhibiting aromatase, an enzyme that catalyses the conversion of androgens to oestrogens . Since prostate cells express aromatase, it is presumed that chrysin blocked androgen conversion into oestrogens, increasing the intraprostatic bioavailability of androgens in male and female gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the freshly dissected lobes were immediately frozen in liquid nitrogen and stored at −80ºC. VP and LP were chosen, respectively, for being the most involuted after castration 19,21,29 and the most affected by prostatitis 25,30‐32 …”
Section: Methodsmentioning
confidence: 99%